1956
DOI: 10.1002/zaac.19562830136
|View full text |Cite
|
Sign up to set email alerts
|

Über die Ionen der Schwefligen Säure in wäßriger Lösung

Abstract: Es wird gezeigt, daß die bisherige Auffassung über die Ionen in freier Schwefliger Säure nicht zutrifft. Durch den spektroskopischen Nachweis von S2O 52−‐Ionen und HSO 3−‐Ionen mit einer SH‐Bindung (SH‐Frequenz) ergibt sich, daß in der freien Schwefligen Säure bezüglich der Ionengleichgewichte ähnliche Verhältnisse wie bei den sauren Sulfitlösungen herrschen. Die daraus resultierenden neuen Aspekte für die Definition der beiden Dissoziationskonstanten der Schwefligen Säure werden kurz erörtert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1956
1956
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Nevertheless, its existence has been taken for granted by most chemists. However, evidence from spectral studies including Raman (1,2), infrared (i.r.) (3,4), and ultraviolet (u.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its existence has been taken for granted by most chemists. However, evidence from spectral studies including Raman (1,2), infrared (i.r.) (3,4), and ultraviolet (u.v.)…”
Section: Introductionmentioning
confidence: 99%
“…The only other species detected in some cases were the HS04-and Sod--ions formed by slow oxidatioil of aqueous SO2, a reaction difficult to prevent during long exposures. Recently an extensive Raman study by Simon and Waldmann (15,16,17) revealed for the first time in these solutions some lines due to bisulphite ions, HSO3-, in very low concentration, as well as pyrosulphite ions, HS206-, pointing to the hitherto unsuspected equilibrium HS03-$ SO2…”
mentioning
confidence: 99%
“…The characteristic lines of BrO; and HSO; decrease, and the lines due to the SO:and HSOZ ions increase in intensity. Formation of protons [reactions (5) and (6)] favours displacement of reactions (1) and (2) to the right, with formation of SOz at the end of the reaction in the presence of excess of sulphite ions. It is apparent that mechanisms (4) and (5) predominate during the initial part of the reaction, while reaction (6) is established as the production of protons by mechanism (5) becomes significant.…”
Section: Applicationmentioning
confidence: 99%
“…The reactions (4), (5) and (6) may be written in the generalized form: The data from the experiment can be treated under the assumption that the reaction follows the rate law: that the reaction is first order in both bromate and total sulphate concentration with k = 3.2 f 0.5 mol-' s-l 1. The increase of the slope observed in the second part of the curve can be explained by the hydrogen ion dependence of the rate.…”
Section: Applicationmentioning
confidence: 99%